This book is anti-racist - Jewell, Tiffany (Frances Lincoln Children's Books, 2020)
Offers young people twenty illustrated lessons with activities for standing up to racism. Provides information on understanding your own identity, personal and institutional racism, the history of prejudice, and ways to take action against racism. Features extensive backmatter including a glossary of terms, notes on the text, and resources for further information.